2017
DOI: 10.1136/annrheumdis-2017-211284
|View full text |Cite
|
Sign up to set email alerts
|

Do depression and anxiety reduce the likelihood of remission in rheumatoid arthritis and psoriatic arthritis? Data from the prospective multicentre NOR-DMARD study

Abstract: Depression and anxiety may reduce likelihood of joint remission based on composite scores in RA and PsA and should be taken into account in individual patients when making a shared decision on a treatment target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
124
1
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 21 publications
10
124
1
18
Order By: Relevance
“…These effects were found to be more pronounced among adult psoriasis patients with pre‐adult onset, with age serving as a moderator of the effect of psoriasis on the degree of psychological impediment . The comorbidity of psoriasis with anxiety and depression was found to affect treatment response, as higher scores of anxiety or depression among psoriasis patients were found to reduce the likelihood of remission after 3 and 6 months of treatment . These results have been summarized recently in a narrative review exploring epidemiological, observational and clinical studies, indicating a substantially greater mental health comorbidity burden in patients with psoriasis compared to those without psoriasis or patients with other dermatologic conditions …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These effects were found to be more pronounced among adult psoriasis patients with pre‐adult onset, with age serving as a moderator of the effect of psoriasis on the degree of psychological impediment . The comorbidity of psoriasis with anxiety and depression was found to affect treatment response, as higher scores of anxiety or depression among psoriasis patients were found to reduce the likelihood of remission after 3 and 6 months of treatment . These results have been summarized recently in a narrative review exploring epidemiological, observational and clinical studies, indicating a substantially greater mental health comorbidity burden in patients with psoriasis compared to those without psoriasis or patients with other dermatologic conditions …”
Section: Introductionmentioning
confidence: 95%
“…5 The comorbidity of psoriasis with anxiety and depression was found to affect treatment response, as higher scores of anxiety or depression among psoriasis patients were found to reduce the likelihood of remission after 3 and 6 months of treatment. 6 These results have been summarized recently in a narrative review exploring epidemiological, observational and clinical studies, indicating a substantially greater mental health comorbidity burden in patients with psoriasis compared to those without psoriasis or patients with other dermatologic conditions. 7 While studies assessing anxiety and depression disorders among patients with psoriasis have focused on determining the unique prevalence of each disorder separately, fewer have addressed the prevalence of their joint presentation.…”
Section: Introductionmentioning
confidence: 99%
“…A 2010 longitudinal population‐based study found chronic arthritis to be associated with mood disorders (ie anxiety or depression) . The prevalence of depressive disorder in RA was 17% (95% CI 10%‐24%), and was found to be associated with poorer outcomes . Improved understanding of the prevalence and impact of mood disorders in patients with RA will lead to early diagnosis and intervention, and improved patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…3 The prevalence of depressive disorder in RA was 17% (95% CI 10%-24%), and was found to be associated with poorer outcomes. 4,5 Improved understanding of the prevalence and impact of mood disorders in patients with RA will lead to early diagnosis and intervention, and improved patient quality of life. Accordingly, the aim of this study was to investigate the prevalence of and factors significantly associated with depression and anxiety in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…К факторам, которые ассоциирова-лись с невозможностью достижения ремиссии, относи-лись женский пол, высокий счет ЧБС, нарушение функ-циональной активности, депрессия, ожирение и артери-альная гипертензия. Данные регистра NOR-DMARD (n=1326) также свидетельствуют о том, что наличие симптомов депрессии и тревоги достоверно снижает шансы на достижение ремиссии [31]. Интересно, что в другом исследовании, выполненном этой группой ав-торов, была отмечена дискордантность между PGA и объективными признаками активности воспаления (ЧБС/ЧПС), что существенно влияло на частоту дости-жения ремиссии [32].…”
unclassified